Prominent role of chemical heterogeneity on cryogenic rejuvenation and thermomechanical properties of La–Al–Ni metallic glass. (August 2019) - Sohrabi, S.; Ri, M.C.; Jiang, H.Y.; Gu, L.; Wen, P.; Sun, Y.H.; Wang, W.H.
Abstract: Structural heterogeneity of metallic glass is critical in cryogenic rejuvenation but chemical heterogeneity is seldom explored. Here we show that cryogenic rejuvenation of a nominal La60 Al25 Ni15 (at.%) metallic glass can be enabled with little impurities of Ce and Fe inside the material. Besides, these impurities can significantly enlarge the plastic strain conveyed by the material in bending. In addition, the heterogeneous structure is observed in the sample containing these chemical heterogeneities. Although the glass forming ability of the metallic glass is worsened, our study highlights the impact of chemical heterogeneity on the cryogenic rejuvenation of metallic glasses. Graphical abstract: Image 1 Highlights: The importance of chemical heterogeneity on cryogenic rejuvenation of metallic glasses. A little impurity can enable energy-increase in La60 Al25 Ni15 (at.%) metallic glass. Plasticity-enhancement of rejuvenated glass.